Inhibition of JNK Mitochondrial Localization and Signaling Is Protective against Ischemia/Reperfusion Injury in Rats - Chambers, Jeremy W. (American Society for Biochemistry and Molecular Biology, 2013)
To build upon recent findings that mitochondrial JNK signaling is inhibited by selectively blocking the interaction between JNK and Sab, we utilized a cell-permeable peptide to demonstrate that ischemia/reperfusion (I/R) injury could be protected in vivo and that JNK mitochondrial signaling was the mechanism by which reactive oxygen species (ROS) generation, mitochondrial dysfunction, and cardiomyocyte cell death occur. We also demonstrated that 5 mg/kg SR-3306 (a selective JNK inhibitor) was able to protect against I/R injury, reducing infarct volume by 34% (p < 0.05) while also decreasing I/R-induced increases in the activity of creatine phosphokinase and creatine kinase-MB. TUNEL staining showed that the percent TUNEL positive nuclei in rat hearts increased 10-fold after I/R injury and that this was reduced 4-fold (p < 0.01) by SR-3306. These data suggest that blocking JNK mitochondrial translocation or JNK inhibition prevents ROS increases and mitochondrial dysfunction and may be an effective treatment for I/R-induced cardiomyocyte death.